She is a haunting - Tran, Trang Thanh (Bloomsbury, 2023)
Seventeen-year-old bisexual Jade Nguyen is spending the summer in Vietnam at the French colonial house her estranged father is fixing up as a vacation rental, but unbeknownst to her family, the house and its ghosts have other plans.